2022
DOI: 10.1021/acsaem.2c02557
|View full text |Cite
|
Sign up to set email alerts
|

Zn-Based Catalysts for Selective and Stable Electrochemical CO2Reduction at High Current Densities

Abstract: Practical electrochemical carbon dioxide (CO 2 ) reduction requires the development of selective and stable catalysts based on low-cost and Earth-abundant materials. In this work, we develop catalysts for CO 2 conversion to CO based on ZnO with various morphologies, including nanoparticles, nanorods, nanosheets, and random shapes. We found that ZnO nanorods exhibit the highest CO 2 to CO efficiency, with a high CO Faradaic efficiency (FE) of over 80% in a current density range of 50−160 mA cm 2 in both flow-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The partial HCOO – formation from the Co-ZnO GDEs is also responsible for hindering the production rate of CO ( j CO ). The ZnO GDE records a maximum j CO of −110 mA cm –2 , which agrees with the material’s already studied ECR performance . The Cu-ZnO catalyst records a maximum j CO of −120 mA cm –2 , indicating that Cu-ZnO is the most active for the ECR and especially for CO formation.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The partial HCOO – formation from the Co-ZnO GDEs is also responsible for hindering the production rate of CO ( j CO ). The ZnO GDE records a maximum j CO of −110 mA cm –2 , which agrees with the material’s already studied ECR performance . The Cu-ZnO catalyst records a maximum j CO of −120 mA cm –2 , indicating that Cu-ZnO is the most active for the ECR and especially for CO formation.…”
Section: Resultssupporting
confidence: 85%
“…The ZnO GDE records a maximum j CO of −110 mA cm −2 , which agrees with the material's already studied ECR performance. 50 The Cu-ZnO catalyst records a maximum j CO of −120 mA cm −2 , indicating that Cu-ZnO is the most active for the ECR and especially for CO formation. As Wan et al described, 45 the material's performance is related to the ECR activity of both the Zn-phase in tandem catalyzing the ECR with the additional Cu-phase.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Numerous studies have demonstrated the effectiveness of pulse electrolysis in stabilizing the conversion of CO 2 to CO (Table ). For example, Stamatelos et al employed an in situ regeneration strategy on ZnO nanorods (ZnO NR) catalysts, which involves periodic oxidations during the electrochemical reduction of CO 2 . The ZnO catalysts undergo significant morphological and oxidation state changes during the ECR process because of the reduction of ZnO to metallic Zn and particle aggregation.…”
Section: Pulse Electrolysis For Stable Ecrmentioning
confidence: 99%
“…(b) Recovery of the ZnO-NR GDE performance by oxidation-CV cycles between −2 and 0.5 V strategy after FE deterioration caused by continuous ECR operation (at 160 mA cm –2 ). (c) Long-term operation of ECR at 160 mA cm 2 with periodic CV cycles between −2 and 1 V (CV2) every 1 h. Reproduced from ref . Copyright 2022 American Chemical Society.…”
Section: Pulse Electrolysis For Stable Ecrmentioning
confidence: 99%